FLUCTUATIONS IN CATCHES KURAU (Eleutheronema tetradactylum) IN BAY PAMBANG VILLAGE, DISTRICT OF BENGKALIS RIAU PROVINCE - Permata, Chita Dwi; Rengi, Pareng (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was carried out in February in 2017 in the Pambang village, district Bantan Bay Regency of Bengkalis Riau Province. This research aims to see fluctuations in catches kurau (Eleutheronema tetradactylum) based on fish production for 5 years, from the year of 2012-2016 and to know the fishing season for kurau by looking kurau fishing season index using survey methods. Influence kurau production, such as 2013 15,778.3 kg, 2014 24,146 kg, 2015 4,233 kg, 2016 4,540.3 kg and that rate uncertain. Based on the value of season index, fishing season for kurau have on November-Maret.Keyword: Fluctuations, season index, fish kurau.